Design and Fabrication of Driver Amplifier for Wilkinson Power Divider Operating at S Band - Chuc, Doan Huu; Giang, Bach Hoang; Long, Hoang Duc; Duong, Bach Gia (VNU Journal of Science: Mathematics - Physics; Vol 29 No 3, 2013)
Abstract. In this paper, we introduce an overview of microwave power transmission system (MPT) including of power transmitter, free space transmission, rectenna. Also, t he paper particularly presents in detail the proposed configuration of power transmitter. The presented power amplifier, which has the output of 1W, is fabricated by using AH201. The 1-Watt amplifier plays an important role as driver amplifier in the configuration.  In addtion, the 4 – way Wilkinson divider/combiner has been designed and manufactured. All simulations and experimental results will be reported. Keywords: Power amplifier, Wilkinson power divider.